The portuguese slave trade in Early Modern Japan: merchants, jesuits and japanese, chinese, and korean slaves - Sousa, Lúcio (2019)
In The Portuguese Slave Trade in Early Modern Japan: Merchants, Jesuits and Japanese, Chinese, and Korean Slaves Lucio de Sousa offers a study on the system of traffic of Japanese, Chinese, and Korean slaves from Japan. Using the Portuguese mercantile networks, de Sousa reconstructs the Japanese communities in the Habsburg Empire; and analyses the impact of the Japanese slave trade on the Iberian legislation produced in the 16th and first half of the 17th centuries.